Can carbon credits fund riparian forest restoration?. Issue 1 (8th December 2014) - Matzek, Virginia; Puleston, Cedric; Gunn, John
Abstract Ecological restoration is increasingly called on to provide ecosystem services (ES) valuable to humans, as well as to benefit biodiversity and improve wildlife habitat. Where mechanisms to pay for ES exist, they may serve as incentives to embark on habitat restoration projects. We evaluated the potential of newly established carbon markets in the United States to incentivize afforestation along riparian corridors, by comparing the income earnable by carbon offset credits with the costs of planting, maintaining, and registering such a restoration project in California. We used a 20‐year chronosequence of riparian forest sites along the Sacramento River as our model project. We found that carbon credits can repay more than 100% of costs after two decades of regrowth, if sufficient effort is put into sampling intensity in the first post‐restoration decade. However, carbon credits alone are unlikely to entice landowners currently engaged in agricultural activities to switch from farming crops to farming habitat.